Intervensi Sosial Untuk Remaja Pengguna TikTok - Rahayu, Gusti; Firman, Firman; Ahmad, Riska (Lembaga Yasin AlSys, 2023)
The high need for the use of technology for teenagers causes them to often spend their time accessing social media. The TikTok application is one of the social media platforms that is accessed and even teenagers make TikTok a place to find identity and self-identity to be recognized by the community of other TikTok users. Social intervention is a form of service that can be provided by counselors to adolescents who cannot filter and limit themselves from the negative impacts of using the TikTok application. Adolescent social interventions will be viewed from a micro, mezzo and macro perspective. So what is expected is that the development of adolescents is properly fulfilled in accordance with the values and norms that apply in society. This article uses literature study as its method.